Methods and Technologies for Exosome Isolation and Characterization. Issue 9 (12th June 2018) - Zhang, Mengdi; Jin, Ke; Gao, Liang; Zhang, Zhengkui; Li, Fang; Zhou, Fangfang; Zhang, Long
Abstract: Exosomes, a specific subclass of the extracellular vesicles secreted by most cell types, play an important role in cell–cell communication by transporting diverse content including protein, mRNA, miRNA, and DNA. This cargo is closely associated with the pathogenesis of most human malignancies. Therefore, it is becoming an urgent demand to be able to isolate exosomes in a simple, efficient, and economical way for scientific research and clinical diagnosis. Here, several conventional and novel nano‐based techniques of exosome isolation and characterization are summarized, and the advantages and disadvantages among them are compared, with the hope that researchers will be provided with an overview in this field to detect and isolate exosomes in a suitable manner, matching the subsequent experiments. Abstract : Exosomes are cell‐derived vesicles that are present in many kinds of cells. There is a need for the optimization of isolation and characterization methods, which can be divided into traditional and nano‐based novel techniques, of exosomes to support the relative research. All of these methods have advantages and limitations, so they can be used for different experimental objectives.